Bifunctional graphene oxide-copper coated nickel mesh and its electrocatalysis towards ethanol production: A preliminary analysis - Othman, M.F.H. (Elsevier B.V., 2020)
The bifunctional Graphene Oxide-Copper (GO-Cu) coated nickel mesh that was fabricated through layer-by-layer approach was used as a working electrode in carbon dioxide (CO2) electro-reduction process for ethanol production. The findings confirmed smooth and well-dispersed deposition of Cu-nanoparticles onto GO, and less corrosion behavior in 0.1 M potassium carbonate (K2CO3) solution. Besides, linear sweep voltammetry and chronoamperometry analysis was performed to determine the electro-reduction activity of the fabricated electrode. Novelty of this study covers a working electrode production that possesses high durability and stability while maintaining good current and proton conductivity, as well as high efficiency and selectivity towards desirable product. Â© 2020 Elsevier B.V.